Managing the Impact of AI in education: strategies for lecturers / Dr. Farah Adilla Ab Rahman and Jeniwaty Mohd Jody - Ab Rahman, Farah Adilla; Mohd Jody, Jeniwaty (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
The rapid advancement of technology, particularly in the realm of Artificial Intelligence (AI), has significantly influenced the education sector. AI-powered tools, such as chatbots and virtual assistants, are increasingly being used to assist students in various aspects of their learning journey (Essel et al., 2022). However, the convenience of accessing instant information through AI platforms may inadvertently lead to complacency among students, affecting their motivation to seek knowledge independently. This essay delves into the challenges posed by AI in education and offers strategies for lecturers to address them, ensuring that AI augments rather than replaces active learning and critical thinking.